ANALISIS BANTUAN SOSIAL DANA CSR (CORPORATE SOCIAL RESPONSIBILITY) KHUSUS BANTUAN DANA SOSIAL PADA PUSAT PEMBANGKIT LISTRIK TENAGA AIR (PLTA) BAKARU KABUPATEN PINRANG - Hernianti Harun; Nurhapisa Nurhapisa (Journal AK-99, 2022)
CSR (Corporate Social Responsibility) is now increasingly popular in its implementation by companies in the world, including in Indonesia. This study aims to find out what social assistance CSR programs are applied to the Bakaru hydropower plant, as well as how to utilize CSR funds at the Bakaru hydropower plant. The subjects of this study were employees who worked at the bakaru hydropower plant and knew a lot about the problems related to the research. The data analysis technique in this study uses a qualitative descriptive of the miles and Huberman model, namely data reduction, data presentation (data display) and conclusion drawing / verification. That is to compare the results of the research with existing theories. The results showed that the Bakaru hydropower plant had implemented CSR social assistance in the nearest area of the company. Such as bakaru village, salimbongan village, pao village. The types of assistance that have been carried out are the distribution of basic necessities, assistance with school supplies, electricity meters, medicine assistance, free examination assistance, computer assistance, Qur'an assistance, assistance for outstanding students, assistance in the procurement of clean water, assistance in electricity vouchers, wage assistance for teachers, and donating land for funerals. However, based on the community's view, the implementation of the hydropower CSR program has not been effective enough because it has not been able to improve the quality of life of the community.